The tadpole of Physalaemus nanus (Boulenger, 1888) (Anura, Leptodactylidae) from Southern Brazil - Ceron, Karoline; Santana, Diego José (Zootaxa, 2017)
The genus Physalaemus Fitzinger, 1826 currently comprises 47 described species distributed from Central America (Guianas) to Uruguay (Frost 2016). The genus has been recently organized in two main clades based on molecular data, Physalaemus signifer Clade and Physalaemus cuvieri Clade (Lourenço et al. 2015). The P. signifer Clade, with 15 species, is composed by the P. deimaticus and P. signifier groups, plus P. nattereri (Steindachner, 1863) and P. maculiventris (Lutz, 1925) (Nascimento et al. 2005; Lourenço et al. 2015).